2022
DOI: 10.21203/rs.3.rs-1197371/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of glycogen synthase kinase-3-beta (GSK3β) blocks nucleocapsid phosphorylation and SARS-CoV-2 replication

Abstract: GSK3β has been proposed to have an essential role in Coronaviridae infection. Screening of a targeted library of GSK3β inhibitors against SARS-CoV-2 and HCoV-229E resulted in identification of high proportion of active compounds with low toxicity to host cells. A select lead compound, T-1686568, showed dose-dependent activity against SARS-CoV-2 transcription, translation and viral particle release in multiple cell lines and primary organoids. A protein kinase substrate profiling assay combined with western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A meta-analysis of clinical data from more than 300,000 COVID-19 patients in three major health systems using a random-effects model revealed a 50% reduction in risks in patients who take lithium which is a direct inhibitor of GSK-3, while in vitro results showed that GSK-3 inhibition effectively impaired viral replication and blocked infection in human lung epithelial cells [ 569 ]. Selective screening of a library of GSK-3β inhibitors found a high proportion of compounds that inhibited GSK-3β were also effective in reducing SARS-CoV-2 infection [ 570 ].…”
Section: Melatonin Disrupts Formation Of “Viral Factories” By Regulat...mentioning
confidence: 99%
“…A meta-analysis of clinical data from more than 300,000 COVID-19 patients in three major health systems using a random-effects model revealed a 50% reduction in risks in patients who take lithium which is a direct inhibitor of GSK-3, while in vitro results showed that GSK-3 inhibition effectively impaired viral replication and blocked infection in human lung epithelial cells [ 569 ]. Selective screening of a library of GSK-3β inhibitors found a high proportion of compounds that inhibited GSK-3β were also effective in reducing SARS-CoV-2 infection [ 570 ].…”
Section: Melatonin Disrupts Formation Of “Viral Factories” By Regulat...mentioning
confidence: 99%